Pengaruh Budaya Organisasi dan Komitmen Organisasi Terhadap Kinerja Pegawai pada Dinas Pertanian Kabupaten Bima - Muhammad Zahrur Ridlo; Mawar Hidayanti; Jaenab Jaenab (INDO PUBLISHING, 2026)
This study aims to determine the influence of organizational culture and organizational commitment on employee performance at the Bima Regency Agriculture Office. This is a quantitative study employing an associative approach. The study population consists of all 173 employees at the Bima Regency Agriculture Office, comprising 73 Civil Servants (PNS), 45 Government Employees with Work Agreements (P3K), and 55 part-time staff. The sample consists of 40 employees holding PNS and P3K status, selected using purposive sampling. The results indicate that organizational culture has a significant influence on employee performance at the Bima Regency Agriculture Office; organizational commitment does not have a significant influence on employee performance at the Bima Regency Agriculture Office; and organizational culture and organizational commitment together have a significant influence on employee performance at the Bima Regency Agriculture Office.